Sleep Quality Is Associated With Severe Meibomian Gland Disruption in Dry Eye - Zhu, Yirui; Huang, Xiaodan; Lin, Lin; Di, Mengshu; Chen, Ruida; Fang, Fei; Jin, Xiuming (Frontiers in Medicine, 2022)
Purpose To investigate the association between sleep quality and meibomian gland dropout characteristics in dry eye patients. Methods This cross-sectional study involved 172 dry eye patients with no history of conditions or factors that could confound dry eye disease (DED) and/or meibomian gland dropout. Participants underwent a comprehensive anterior eye assessment. The validated Athens Insomnia Scale (AIS) and Pittsburgh Sleep Quality Index (PSQI) were used to assess sleep quality. The measured outcomes were dry eye symptoms via the Ocular Surface Disease Index (OSDI), tear breakup time (TBUT), corneal fluorescein staining, meibomian gland function, and extent of meibomian gland dropout. Results Of the dry eye participants, 34.9% had severe meibomian gland dropout (SMD) and 41.3% of the subjects had poor sleep quality. Patients with poor sleep quality had greater Meibomian gland dropout while the sleep AIS and PSQI scores were significantly correlated with Meibomian gland dropout (r = 0.495, p < 0.001; r = 0.24, p = 0.002; respectively). SMD patients had worse scores on all components of the PSQI (all p < 0.001, corrected for age and sex). Use of sleep medication, poor habitual sleep efficiency, and sleep disturbance were particularly prevalent in SMD patients as compared to Non-severe meibomian gland dropout (NSMD) patients. Multivariate logistic regression analysis revealed that sleep quality was eventually associated with female gender (p = 0.042), OSDI (p = 0.004), TBUT (p = 0.036), and Meibomian gland dropout score (p < 0.001). Conclusion It was found that greater meibomian gland dropout in poor sleep quality individuals is especially related to use of sleep medication, poor habitual sleep efficiency, and sleep disturbance. This finding suggests a need for long-term studies of anterior eye health in people with poor sleep quality.